The impact of COVID‐19 on the sensitivity of D‐dimer for pulmonary embolism. (23rd August 2021) - Elberts, Samuel J.; Bateman, Ryan; Koutsoubis, Alexandra; London, Kory S.; White, Jennifer L.; Fields, J. Matthew
Abstract: Objective: This study seeks to evaluate the test characteristics of D‐dimer for pulmonary embolism (PE) in patients with a concurrent diagnosis of COVID‐19. We hypothesized that the sensitivity of D‐dimer for PE at current institutional cut points would be similar to those without COVID‐19. Methods: This is a multicenter retrospective observational cohort study across five urban and suburban EDs in the same health care system. The electronic health record was queried for all computed tomography pulmonary angiography (CTPA) studies from December 1, 2019, to October 22, 2020. All ED patients who underwent CTPA had D‐dimer and COVID‐19 testing completed in a single encounter were included in the study. Baseline demographics were obtained. Test characteristics of D‐dimer for PE were calculated for patients with and without COVID‐19. Additionally, receiver operator characteristics (ROC) curves were constructed for two different D‐dimer assays. Results: There were 1158 patient encounters that met criteria for analysis. Performance of D‐dimer testing for PE was similar between COVID‐19–positive and –negative patients. In COVID‐19–positive patients, the sensitivity was 100% (95% confidence interval [CI] = 87.6%–100%), specificity was 11.9% (95% CI = 7.9%–17.1%), and negative predictive value (NPV) was 100%. In COVID‐19–negative patients the sensitivity was 97.6% (95% CI = 91.5%–99.7%), specificity was 14.4% (95% CI = 12.1%–17%), and NPV was 98.3% (95% CI = 93.8%–99.6%). For assay 1 the area under the curve (AUC) for COVID‐19–positive patients was 0.76 (95% CI = 0.68–0.83), and for COVID‐19–negative patients, 0.73 (95% CI = 0.69–0.77). For assay 2, AUC for COVID‐19–positive patients was 0.85 (95% CI = 0.77–0.92), and for COVID‐19–negative patients, 0.80 (95% CI = 0.77–0.84). Inspection of the ROC curve for assay 1 revealed that 100% sensitivity was maintained up to a threshold of 0.67 FEU (fibrinogen equivalent units; from 0.50 FEU) with an increase in specificity to 29% (from 18.7%), and for assay 2, 100% sensitivity was maintained up to a threshold of 662 D‐dimer units (DDU; from 230 DDU) with an increased specificity to 59% (from 6.1%). Conclusion: Results from this multicenter retrospective study did not find a significant difference in sensitivity of D‐dimer for PE due to concomitant COVID‐19 infection. Further study is required to determine if PE can safely be excluded based on D‐dimer results alone in patients with suspected or proven COVID‐19 or if adjusted D‐dimer levels could have a role in management.